High performance InGaAs channel MOSFETs on highly resistive InAlAs buffer layers. (February 2021) - Lee, Sang Tae; Lee, In-Geun; Jang, Hyunchul; Kong, Minwoo; Song, Changhun; Kim, Chang Zoo; Jung, Sang Hyun; Choi, Youngsu; Kim, Shinkeun; Eom, Su-keun; Seo, Kwang-seok; Kim, Dae-Hyun; et al.
Highlights: High resistivity InAlAs buffer layer growth using by MOCVD. Performance improvement of InGaAs channel MOSFETs using high resistivity InAlAs buffer. Influence of resistance characteristics of InAlAs buffer by impurity atoms. Compensation effect of residual carriers by oxygen-related deep donor. Abstract: We investigated the effect of growth temperature on the structural and electrical properties of InAlAs layers grown on InP (1 0 0) substrates by metalorganic chemical vapor deposition (MOCVD) method. Flat surface morphology of InAlAs layers with root mean square (RMS) surface roughness values below 0.4 nm were obtained at 500 °C and 660 °C, while RMS surface roughness values of InAlAs layers grown in the region of intermediate temperature increase from 0.7 nm at 540 °C to 3.9 nm at 620 °C with increasing growth temperature. This increase in surface roughness is caused by the phase separation of the InAlAs layer, which is divided into In-rich and Al-rich column regions. The resistivity values of the InAlAs layers grown at 500 °C and 660 °C, in which the phase separation was not observed, were analyzed by the transmission line method (TLM) and those values were 1 × 10 4 Ω·cm and 0.06 Ω·cm, respectively. We propose that oxygen atoms being incorporated into InAlAs layers during growth were the cause effect explaining the change in resistivity depending on the growth temperature. In order to evaluate high-resistivity InAlAs layers grown at 500 °C for a buffer layer of devices, we fabricated InGaAs-channel metal oxide field effect transistors (MOSFETs). The on/off current ratio values obtained from ID -VG transfer measurement was a value of 6.10 × 10 5, indicating a high-performance characteristic.